Ethno-education in rural communities: School San José de Ure, in Córdoba, Colombia. A case study - Castro Puche, Rubby Cecilia; Taborda Caro, María Alejandra; Londoño Agudelo, María Yovadis (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
In this research, we aim to study the complexity of the ethno-education model from the following perspectives: the rural education, the new version of rurality, the actors, and the ethno-educative institution located in the rural context of the Córdoba department, in Colombia. This research work was carried out in order to analyze the reality that underlies the implementation of differential education achievement, which is the right of the Colombian ethnic groups, in the context of a hegemonic education represented by the rural education and the program known as New School, in the case of the educative institution named “San José de Uré”. The ethnographic approach was applied and this revealed the dynamic of an ethno-educative institution where converges both realities: rural and ethnic-Afro. As a consequence of this complex scenario, we found epistemological challenges and several questions which highlight the incongruence of rural education with regards to ethno-education. From this perspective, we identify some problems that make complex both processes. As a corollary, we present the discussion of findings and reflections.